Microbial soil community analyses for forensic science: Application to a blind test. (January 2017) - Demanèche, Sandrine; Schauser, Leif; Dawson, Lorna; Franqueville, Laure; Simonet, Pascal
Highlights: RISA or HTS on soil DNA succeeded to identify soil samples from single origin. A combination of methods was necessary to correctly identify samples from mixed origin. Soil DNA could be a useful tool for forensic science. Abstract: Soil complexity, heterogeneity and transferability make it valuable in forensic investigations to help obtain clues as to the origin of an unknown sample, or to compare samples from a suspect or object with samples collected at a crime scene. In a few countries, soil analysis is used in matters from site verification to estimates of time after death. However, up to date the application or use of soil information in criminal investigations has been limited. In particular, comparing bacterial communities in soil samples could be a useful tool for forensic science. To evaluate the relevance of this approach, a blind test was performed to determine the origin of two questioned samples (one from the mock crime scene and the other from a 50:50 mixture of the crime scene and the alibi site) compared to three control samples (soil samples from the crime scene, from a context site 25 m away from the crime scene and from the alibi site which was the suspect's home). Two biological methods were used, Ribosomal Intergenic Spacer Analysis (RISA), and 16S rRNA gene sequencing with Illumina Miseq, to evaluate the discriminating power of soil bacterial communities. Both techniques discriminated well between soils from a single source, but a combination of both techniques was necessary to show that the origin was a mixture of soils. This study illustrates the potential of applying microbial ecology methodologies in soil as an evaluative forensic tool.